Penggunaan Media KOKUBA untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa SD - Udmah, Syafaatul; Purwaningrum, Jayanti Putri; Ermawati, Diana (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
Mathematics learning is one of the subjects that is considered difficult, learning without the use of learning media and only the use of lecture learning methods, resulting in low mathematical thinking skills of students. This is based on the results of the precycle carried out with an average score of 50.47 in classical problem solving ability with criteria for needing guidance. The purpose of this study is to improve mathematical problem solving skills and student learning activities in mathematics learning for grade V elementary school students. The method in this study is classroom action research (PTK) with the use of cycles of planning, action, observation and reflection. The results of research using the KOKUBA-assisted an increase in mathematical problem solving ability in cycles I and II, cycle I of 81.56 with good criteria with a percentage of completeness of 81.25% and an increase in cycle II to 91.5 with very good criteria with a percentage of completeness of 93.75%. Based on the research, it was concluded that there was an increase in the ability to solve class V mathematical problems through KOKUBA media.